Cash Sales Accounting Information System Design Using “Small and Medium Enterprises Accounting” and “Sales Notes” Applications at Senja Store - Inadia Zahra Ratrisha; Ditya Permatasari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
In this millennial era, technological developments and the role of computerized accounting information systems are very important. Competition between businesses is now so tight, the more advanced a business is, the more the business is required to improve the quality of work, service quality, and accuracy in processing data. Companies also need a good information system. The purpose of the accounting information system itself is to complete every obligation that is by the authority given to someone, useful for management decision making, and support the smooth operation of business every day (Mardi, 2011). The purpose of this study was to determine the design of cash sales accounting information systems at UD. Senja Batu City. The type of research used is descriptive qualitative. With data collection techniques, namely interviews, observation, and documentation. The results in this study are 1) UD. Senja in its operational activities in its entirety still uses a manual system. 2) the absence of a warehouse and accounting department in UD. Senja. 3) The author recommends a cash sales accounting information system at UD. Senja, which contains accounting documents and records, related functions, and cash sales procedures at UD. Senja. 4) Application recommendations for making sales notes and accounting records related to cash sales transactions.